Evaluation of plan quality based on a novel plan difficulty index and its preliminary application in radiotherapy. Issue 1 (1st January 2021) - Li, Qicheng; Luo, Huanli; Liu, Xianfeng; Zhong, Mingsong; Yang, Han; Tao, Dan; Jin, Fu
ABSTRACT: To propose a novel plan difficulty index (PDI) and scoring model and evaluate its application in intensity-modulated radiation therapy (IMRT) plans for lung cancer. Thirty-four optimal IMRT plans of lung cancer were retrospectively analyzed. These plans have been clinically implemented to treat patient. Four scoring models, segmented uniform (SU), segmented non-uniform (SNU), non-segmented uniform (NSU) and non-segmented non-uniform (NSNU), containing 12 metrics, were designed for plan evaluation. A novel PDI was defined to quantify how easy or difficult a treatment plan is to make and verify the rationality of scoring models, followed by the evaluation of the relationship between PDI and scoring value of plan. Significant differences were found between different scoring models. These scores were 72.34 ± 10.10, 69.40 ± 12.06, 53.11 ± 10.44 and 50.30 ± 11.67 for SU, SNU, NSU and NSNU models, respectively. The pass rate (64.7%) of plans with scores of ≥70 was superior in the SU model compared to that of other models (SNU: 38.2%, NSU: 5.9%, and NSNU: 2.9%). The mean PDI of 34 plans was 4.20 for the uniform scoring model and 4.47 for the non-uniform scoring model. Negative correlations were shown between PDI and scores [SU: −0.52 ( P < 0.05), SNU: −0.49 ( P < 0.05), NSU: −0.59 ( P < 0.05), and NSNU: −0.53 ( P < 0.05)]. PDI is feasible for IMRT plan evaluation for lung cancer, and the SU scoring model was superior to NSU, SNU, and NSNU models in clinical practice.